Near-Infrared to T-Ray Frequency Conversion Using Kagome Photonic Crystal Resonators - Deepika Tyagi; Vijay Laxmi; Ahsan Irshad; Abida Parveen; Mehboob Alam; Yibin Tian; Zhengbiao Ouyang (Nanomaterials)
Kagome lattices have attracted significant research interest due to their unique interplay of geometry, topology, and material properties. They provide deep insights into strongly correlated electron systems, novel quantum phases, and advanced material designs, making them fundamental in condensed matter physics and material engineering. This work presents an efficient method for terahertz (THz) wave generation across the entire THz spectrum, leveraging high-quality-factor Kagome-shaped silicon photonic crystal resonators. In the proposed simulation-based approach, an infrared (IR) single-frequency wave interacts with an induced resonance mode within the resonator, producing a THz beat frequency. This beat note is then converted into a standalone THz radiation (T-ray) wave using an amplitude demodulator. Simulations confirm the feasibility of our method, demonstrating that a conventional single-frequency wave can induce resonance and generate a stable beat frequency. The proposed technique is highly versatile, extending beyond THz generation to frequency conversion in electronics, optics, and acoustics, among other domains. Its high efficiency, compact design, and broad applicability offer a promising solution to challenges in THz technology. Furthermore, our findings establish a foundation for precise frequency manipulation, unlocking new possibilities in signal processing, sensing, detection, and communication systems.